Japanese clematis, Clematis terniflora (D.C.) Ranunculaceae - Michael Meisenburg; Ken Langeland; Kurt Vollmer (EDIS)
SS-AGR-309, a 4-page illustrated fact sheet by Michael Meisenburg, Ken Langeland, and Kurt Vollmer, describes this vigorous woody vine that is recommended for landscape use in cold-hardy zones, but is considered invasive in many areas of the country — its impacts and management. Includes references. Published by the UF Department of Agronomy, September 2008.